(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In this paper, the design of a prototype of Remote Control (RC) aircraft is discussed. It is important and interesting to learn about the workings, terminology, factors affecting to flight, construction, application, and advantage of the aircraft. Also, studied about the designing aeronautics formula rules and analytical equations of aircraft lift force and drag force of a RC airplane for AOA analysis. In addition, aerodynamic performance is carried out on the airfoil type wing to determine the drag and lift forces at maximum speed.